A new target of radiotherapy combined with immunotherapy: regulatory T cells - Song, Dongmei; Ding, Yun (Frontiers in Immunology, 2024)
Radiotherapy is one important treatment for malignant tumours. It is widely believed today that radiotherapy has not only been used as a local tumour treatment method, but also can induce systemic anti-tumour responses by influencing the tumour microenvironment, but its efficacy is limited by the tumour immunosuppression microenvironment. With the advancement of technology, immunotherapy has entered a golden age of rapid development, gradually occupying a place in clinical tumour treatment. Regulatory T cells (Tregs) widely distributing in the tumour microenvironment play an important role in mediating tumour development. This article analyzes immunotherapy ， the interaction between Tregs, tumours and radiotherapy. It briefly introduces immunotherapies targeting Tregs, aiming to provide new strategies for radiotherapy combined with Immunotherapy.